Association between prescribed central nervous system depressant drugs, comorbidity and cognition among hospitalised older patients: a cross-sectional study - Espen Saxhaug Kristoffersen; Christofer Lundqvist; Socheat Cheng; Tahreem Ghazal Siddiqui; Michael Gossop; Ramune Grambaite (BMJ Open)
Objectives Central nervous system depressants (CNSDs) such as opioids, benzodiazepine and Z-hypnotics are commonly used. However, CNSDs may influence cognitive function, especially in older hospitalised patients with comorbidities. The aim was to examine the association between CNSD use and cognitive function in older patients. We assessed global and domain specific cognitive function, among hospitalised older patients, including covariates for comorbidity, anxiety and depression.Design Cross-sectional hospital-based study.Settings Data was collected consecutively from inpatients at somatic wards of a general university hospital.Participants Older patients between 65 and 90 years with/without CNSD use for ≥4 weeks.Outcome measures The main outcome was cognitive function assessed by Cognistat. Secondary outcomes were routine clinical tests in the wards (mini-mental state examination (MMSE), trail making test (TMT) A and B, and clock drawing tests). Analyses were bivariate and multiple linear regression, adjusted for age, gender, and education. Covariates were comorbidity, depression and anxiety scores.Results The main result indicated that CNSD users (n=100) had (β=–3.4, 95% CI 6.27 to –0.58, p=0.017) lower Cognistat score than non-users (n=146), adjusted for age, gender, education, anxiety and depression, but not significant when including covariate for comorbidity (β= –2.50 - 5.45; –0.46, p=0.097). Comorbidity was associated with cognitive function (β=−0.77, 95% CI −1.22 to −0.14, p=0.014). Cognistat subdimensions associated with CNSD use were language (p=0.017) and calculation (p=0.003). In clock drawing test, users had lower scores than non-users (β=−0.80, 95% CI 1.24 to −0.36, p=0.004), but no significant difference was found with MMSE and TMT A or B. Z-hypnotics were associated with reduced cognitive function.Conclusion Among older hospitalised patients, global cognition and specific cognitive functions were associated with long-term use of CNSD medication as well as with somatic comorbidity.Trial registration number NCT03162081, 22 May 2017.